2020
DOI: 10.1159/000505601
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Gray Matter Volume and Cortical Surface in Paranoid-Type Delusional Disorder

Abstract: Introduction: Delusions are core symptoms of schizophrenia-spectrum and related disorders. Despite their clinical relevance, the neural correlates underlying such phenomena are unclear. Recent research suggests that specific delusional content may be associated with distinct neural substrates. Objective: Here, we used structural magnetic resonance imaging to investigate multiple parameters of brain morphology in patients presenting with paranoid type delusional disorder (pt-DD, n = 14) compared to those of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 99 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…In fact, in schizophrenia patients with psychomotor inhibition, we found reduced grey matter volume and increased resting-state perfusion in the supplementary motor area across samples, who in turn demonstrated increased rs-fc and structural connectivity with other motor areas of the brain [71][72][73][74][75]. The brain alterations in patients with paranoia follow a similar pattern: reduced grey matter volumes in amygdala and ventral striatum [13,76], increased restingstate perfusion of the amygdala [14,15], and increased rs-fc within a limbic network. Thus, specific alterations of cerebral circuit physiology may give rise to distinct symptoms in psychosis.…”
Section: Discussionmentioning
confidence: 61%
“…In fact, in schizophrenia patients with psychomotor inhibition, we found reduced grey matter volume and increased resting-state perfusion in the supplementary motor area across samples, who in turn demonstrated increased rs-fc and structural connectivity with other motor areas of the brain [71][72][73][74][75]. The brain alterations in patients with paranoia follow a similar pattern: reduced grey matter volumes in amygdala and ventral striatum [13,76], increased restingstate perfusion of the amygdala [14,15], and increased rs-fc within a limbic network. Thus, specific alterations of cerebral circuit physiology may give rise to distinct symptoms in psychosis.…”
Section: Discussionmentioning
confidence: 61%
“…The sqrtsulc is defined as the square root‐transformed sulcus depth based on the Euclidean distance between the central surface and its convex hull (Gaser & Dahnke, 2016). A previous study reported that the top discriminative features for ADHD were in cortical areas (Sun et al, 2018), and the surface values were associated with multiple brain diseases (Al‐Radaideh et al, 2019; Madeira et al, 2020; Wolf et al, 2020; Zheng et al, 2019). The discriminative ability of the four surface values for the diagnosis of ADHD has not been investigated until now.…”
Section: Introductionmentioning
confidence: 99%
“…The present study expands research on SPA (Horvath et al., 2020; Schmitgen et al., 2020) by addressing two major objectives: First, we sought to investigate two structural markers of cortical development that have distinct evolutionary and genetic origins in SPA and n‐SPA individuals: complexity of cortical folding (CCF) and cortical thickness (CTh). CTh is a dynamic parameter that undergoes postpartum changes with nonlinear trajectories of development often being modulated by environmental stimuli (Hirjak et al., 2016; Wierenga et al., 2014; R. C. Wolf et al., 2020). In contrast, CCF is a stable marker of neurodevelopmental process, as it becomes manifest at weeks 10–16 of gestation and undergoes only minor changes after the third trimester (Armstrong et al., 1995; Hirjak et al., 2016; N. D. Wolf et al., 2020).…”
Section: Introductionmentioning
confidence: 99%